Innovative Practice Report on Nurse-led Interfaith Symbol Translation and Adaptive Clinical Nursing Technology: A Qualitative Interview-based Study - Zou, Zhenyu; Zhai, Bingyan (Asian Pacific Journal of Cancer Care, 2026)
Introduction: To summarize and analyze the innovative, culturally adaptive interventions developed and implemented by frontline oncology nurses to resolve conflicts between patients’ religious practices and clinical care protocols. Materials and Methods: Semi-structured interviews were conducted with nurses working in a hospital oncology department. The interviews focused on documenting real-world challenges and the practical solutions nurses created in response to patients’ religious needs. Through thematic analysis of the interview data, three representative cases were summarized, detailing the nurses’ interventions for Buddhist chanting, Muslim Ramadan fasting, and Christian cross-holding. Results: The analysis documented several nurse-led interventions that successfully resolved clinical conflicts. To manage chanting-induced blood pressure fluctuations, nurses developed and introduced a “mantra counting breathing card” to guide rhythmic breathing. For a fasting Muslim patient at risk of hypoglycemia, nurses designed and implemented a sunset-centered, time-phased intravenous infusion schedule. In the case of ECG interference from a metal cross, nurses innovated by applying a medicalgrade silicone pad to shield the object, which eliminated the artifact. These nurse-initiated solutions were reported to enhance patient compliance and psychological comfort. Conclusion: This study summarizes a transferable framework for faith-sensitive care derived directly from the clinical innovations of frontline nurses. It demonstrates that nurses are pivotal agents in culturally adaptive care, capable of creatively translating religious symbols into safe clinical practices. By documenting and systematizing these grassroots innovations, this research provides a model for leveraging existing nursing expertise to reconcile cultural needs with medical requirements, promising improved patient-centered outcomes in multi-faith settings.